A rapid antimicrobial photodynamic water treatment strategy utilizing a xanthene dye with subsequent removal by Goethite Nanoparticles. (October 2021) - Doyle, Sean; Meade, Elaine; Gao, Jinhui; O'Hagan, Barry; Callan, John F.; Garvey, Mary; Fowley, Colin
Abstract: Although widely accepted as a water sterilisation technique, chlorination results in the production of potentially harmful by-products, mainly Trihalomethanes. Furthermore, the chlorination process requires specialised infrastructure, management and high costs. In this research paper a potential alternative sterilisation technique was investigated. This rapid three-step process utilized Goethite Nanoparticles and the photosensitising capabilities of a xanthene dye. Rose Bengal (RB) a compound primarily used as a stain to diagnose damaged tissue in the eye was utilized under visible light excitation to sterilise water containing gram-positive Staphylococcus aureus and Bacillus cereus. Bacterial reductions (cfu/ml) of up to 6log10 are reported at RB concentrations of 0.5 mg/L and 10 mg/L for S. aureus and B. cereus, respectively. Goethite Nanoparticles (GNP's), an iron oxyhydroxide, were synthesised by co-precipitation of iron salts and used to adsorb RB post-sterilisation. Poly-vinyl Alcohol (PVA) functionalised GNP's were synthesised to highlight the adsorbent capabilities of the GNP surface. The adsorption capacity for uncoated GNPs was 476.19 mg/g, this reduced to 170.4 mg/g for PVA-GNP's, highlighting the highly porous nature of the synthesised GNP surface. Adsorption was optimal in slightly acidic conditions (pH5-6). The adsorption parameters best followed Lagergens Pseudo-second order kinetics with correlation coefficients close to unity. At the highest envisaged RB concentration (10 mg/L) approximately 20 mg/L GNP's was required to remove the dye from solution post-treatment. Flame Atomic Absorption analysis of the water post-removal revealed Iron concentrations of 0.058 mg/L. This correlates to removal efficacy of 99.71% with residual iron levels below the EU recommended limit of 0.2 mg/L. Graphical abstract: Image 1 Highlights: Magnetic nanoparticle/Photosensitiser combination for sterilized water. Photocatalytic Bacterial reductions of 6 log utilizing two Gram-positive strains . Porous goethite nanoparticles with a maximum adsorption capacity of 467.62 mg/g. Minimal Photosentizer or nanoparticle residues post treatment. Nano Particle Removal efficiency of 99.71%.